Laughter yoga as an enjoyable therapeutic approach for glycemic control in individuals with type 2 diabetes: A randomized controlled trial - Hirosaki, Mayumi; Ohira, Tetsuya; Wu, Yawei; Eguchi, Eri; Shirai, Kokoro; Imano, Hironori; Funakubo, Narumi; Nishizawa, Hitoshi; Katakami, Naoto; Shimomura, Iichiro; Iso, Hiroyasu (Frontiers in Endocrinology, 2023)
Background: Laughter has been reported to have various health benefits. However, data on the long-term effects of laughter interventions on diabetes are limited. This study aimed to investigate whether laughter yoga can improve glycemic control among individuals with type 2 diabetes. Methods: In a single-center, randomized controlled trial, 42 participants with type 2 diabetes were randomly assigned to either the intervention or the control group. The intervention consisted of a 12-week laughter yoga program. Hemoglobin A1c (HbA1c), body weight, waist circumference, psychological factors, and sleep duration were evaluated at baseline and week 12. Results: Intention-to-treat analysis showed that participants in the laughter yoga group experienced significant improvements in HbA1c levels (between-group difference: −0.31%; 95% CI −0.54, −0.09) and positive affect scores (between-group difference: 0.62 points; 95% CI 0.003, 1.23). Sleep duration tended to increase in the laughter yoga group with a between-group difference of 0.4 hours (95% CI −0.05, 0.86; P = 0.080). The mean attendance rate for laughter yoga program was high (92.9 %). Conclusions: A 12-week laughter yoga program is feasible for individuals with type 2 diabetes and improves glycemic control. These findings suggest that having fun could be a self-care intervention. Further studies with larger numbers of participants are warranted to better evaluate the effects of laughter yoga. Trial Registration: The University Hospital Medical Information Network Clinical Trials Registry (no. UMIN000047164)